Cost-Effectiveness Analysis of Nivolumab Plus Ipilimumab vs. Chemotherapy as First-Line Therapy in Advanced Non-Small Cell Lung Cancer - Hu, Huabin; She, Longjiang; Liao, Mengting; Shi, Yin; Yao, Linli; Ding, Dong; Zhu, Youwen; Zeng, Shan; Carbone, David P.; Huang, Jin (Frontiers in Oncology, 2020)
ABSTRACT Background: The CheckMate 227 trial has indicated that nivolumab plus ipilimumab compared with chemotherapy significantly increases long-term survival in the first-line setting of advanced non-small-cell lung cancer (NSCLC). Methods: A Markov model was developed to estimate cost and effectiveness of nivolumab plus ipilimumab versus chemotherapy as the first-line therapy in patients with advanced NSCLC based on outcomes data from the CheckMate 227 trial. Cost and health outcomes were estimated at a willingness-to-pay (WTP) threshold of 150000 per quality adjusted life year (QALY) in populations with different programmed death ligand 1 (PD-L1) expression levels (≥50%, ≥1% and <1%) or a high tumor mutational burden (TMB) (≥10 mutations per megabase). Sensitivity analysis were used to test the model stability. Results: The incremental costs and QALYs that nivolumab plus ipilimumab yielded, compared with chemotherapy, were 124180.76 and 1.16, 70951.42 and 0.53, 144093.63 and 0.83 for the advanced NSCLC patients with a PD-L1 expression ≥50%, ≥1% and <1%, leading an incremental cost-effective ratio (ICER) of 107403.72, 133732.20 and 172589.15 per QALY, respectively. For patients with a high TMB, nivolumab plus ipilimumab provided an additional 2.04 QALYs, at a cost of 69182.50 per QALY. Conclusion: Nivolumab plus ipilimumab as first-line therapy is a cost-effective strategy compared with chemotherapy in advanced NSCLC patients with PD-L1 expression levels ≥50% and ≥1% or a high TMB, at a willingness-to-pay threshold of 150000 per QALY, but not in the patients with a PD-L1 expression <1%.